2020
DOI: 10.1111/jep.13353
|View full text |Cite
|
Sign up to set email alerts
|

Re‐assessing the validity of the Moral Sensitivity Questionnaire (MSQ): Two new scales for moral deliberation and paternalism

Abstract: Rationale, aims, and objectives The current study and previous research have called the six‐component model of Lützen's 30‐item Moral Sensitivity Questionnaire (MSQ) into question. For this reason, we re‐examined the construct validity of this instrument. Methods In this cross‐sectional study, which was based on a convenience sample of Dutch nurse practitioners (NPs) and physician assistants (PAs), we tested the validity of MSQ items using exploratory and confirmatory factor analyses (EFA and CFA, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The dataset used in the current study was the same as the one in previous studies by Kuilman and colleagues [12,16,17]. Variables from that pool were used in the present study but were used to address different hypotheses.…”
Section: Methods Study Design Participants and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset used in the current study was the same as the one in previous studies by Kuilman and colleagues [12,16,17]. Variables from that pool were used in the present study but were used to address different hypotheses.…”
Section: Methods Study Design Participants and Data Collectionmentioning
confidence: 99%
“…In an earlier study, we found that PAs and NPs adhere to one of the two types of attitudes when encountering a patient: moral deliberate (MSQ-DELIB) and paternalistic (MSQ-PATER) attitude [12]. We defined moral deliberation as a type of medico-ethical decision-making act to help patients determine the best health-related values realised in the clinical situation after considerable deliberation.…”
Section: Moral Deliberation and Paternalism As Predictors Of Moral Ac...mentioning
confidence: 99%
“…The dataset used in the current study was the same as the one in previous studies by Kuilman and colleagues 18,19 . Different variables were used from that pool, however, the current study focused on different research questions.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset used in the current study was the same as the one in previous studies by Kuilman and colleagues. 18 , 19 Different variables were used from that pool, however, the current study focused on different research questions. In one previous study (Kuilman et al), the “Ethics Advocacy Scale” (EAS) and the scale for “Behavioral Control targeted at Preventing Harm” (BCPH) were used for the purpose of convergent and discriminant validation.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 A healthcare professional with a superior ethical sensitivity is more likely to be able to decide what is best for the patient. 12 High ethical sensitivity not only serves to resolve ethical dilemmas or justify actions but also serves to prevent ethical dilemmas and conflicts. 13 Also called "moral blindness"; a lack of ethical sensitivity leads to violations of patient rights, causes adverse health consequences, and causes the health professional to feel distressed.…”
mentioning
confidence: 99%